Regular paracetamol in severe dengue: a lethal combination? - Lee, W.S.; Gan, C.S.; Chong, S.Y.; Lum, L.C.S. (Stamford Publishing Pte Ltd, 2013)
An eight-month-old female infant with severe dengue disease, who was repeatedly given therapeutic paracetamol for severe dengue, developed fulminant liver failure with encephalopathy, gastrointestinal haemorrhage and severe coagulopathy. She responded to supportive measures and N-acetylcysteine infusion. This case highlights the potential danger of administering repeated therapeutic doses of paracetamol in childhood severe dengue disease with hepatitis.